Impact of MET status on treatment outcomes in papillary renal cell carcinoma: A pooled analysis of historical data. (July 2022) - Albiges, Laurence; Heng, Daniel Y.C.; Lee, Jae Lyun; Walker, Stephen; Mellemgaard, Anders; Ottesen, Lone; Frigault, Melanie M.; L'Hernault, Anne; Wessen, Jonathan; Choueiri, Toni; Cancel, Mathilde; Signoretti, Sabina
Abstract: Background: Papillary renal cell carcinoma (PRCC) represents 15% of RCCs but has no indicated therapies, with limited biomarker-based data to inform targeted treatment. MET alterations may be key; > 80% of PRCC tumours show MET upregulation. The objective of this study was to assess MET status in PRCC and its impact on clinical outcomes. Methods: This retrospective, observational study included patients with locally advanced/metastatic PRCC from three international registries. MET status was determined retrospectively by next generation sequencing (NGS) of archival tissue. MET -driven was defined as MET and/or hepatocyte growth factor amplification, chromosome 7 gain, and/or MET kinase domain mutations. Objectives included progression-free survival (PFS) and overall survival (OS) by MET status using a Cox proportional hazards model. Results: Of 308 patients, 305 received first-line treatment; most commonly sunitinib (n = 208; 68%), then everolimus (n = 40; 13%). Of 179 patients with valid NGS results, 38% had MET -driven and 49% MET -independent tumours (13% unevaluable). In the MET -driven versus MET -independent subgroups, respectively, of sunitinib-treated patients, median PFS was numerically longer, though not statistically significantly; PFS: 9.2 months (95% confidence interval [CI]: 5.4–13.2) versus 5.7 months (95% CI: 4.3–7.4), hazard ratio (HR) = 0.67; 95% CI: 0.41–1.08. There was no difference between the OS of each subgroup. Conclusions: MET -driven PRCC may respond to targeted agents. However, the presence of MET alterations did not appear to be predictive for outcomes in response to current therapies, which are not biomarker-driven, compared with MET -independent tumours. Highlights: This was a retrospective, observational, molecular epidemiology study. Patients had locally advanced/metastatic PRCC that was MET-driven/MET-independent. Patients with MET-driven tumours had numerically longer PFS and TTF versus MET-independent. However, there was no difference in OS between the two groups. MET-driven tumours may not predict poorer outcome versus MET-independent tumours.